Reversible cardiac dysfunction after venlafaxine overdose and possible influence of genotype and metabolism. (September 2016) - Castanares-Zapatero, Diego; Gillard, Nathalie; Capron, Arnaud; Haufroid, Vincent; Hantson, Philippe
Highlights: Large venlafaxine (VEN) overdoses may induce serious cardiac adverse events. VEN is biotransformed by CYP 2D6 and 2C19 isoenzymes to O -desmethylvenlafaxine (ODV). Cardiotoxicity may be observed after sustained exposure to ODV. ODV accumulation is possible even in extensive CYP 2D6 and 2C19 metabolizers. Abstract: Acute poisoning by large venlafaxine (VEN) overdoses may result in serious cardiac events like acute left ventricular dysfunction or even fatalities. In humans, venlafaxine is biotransformed for the most part by CYP2D6 and CYP2C19 isoenzymes to its major metabolite O -desmethylvenlafaxine (ODV), and in parallel to N -desmethylvenlafaxine (NDV) and N, O -didesmethylvenlafaxine (NODV) by several CYP isoenzymes, mainly including CYP3A4 and CYP2C19. The ODV concentrations must be taken into consideration along with those of VEN when relating blood concentrations to clinical effects. Herein we describe a case of reversible cardiac dysfunction following VEN self-poisoning. The peak ODV concentration (46, 094 ng/mL) was observed 20 h post-ingestion, being one of the highest ever associated with survival. The calculated elimination half-life was 10 h for VEN and 22 h for ODV, and the calculated ODV/VEN metabolic ratio 12.9. Genotyping confirmed the patient to have an extensive metabolizer phenotype for CYP2D6, and an ultra-rapid metabolizer phenotype for CYP2C19. We suspect cardiotoxicity was related to sustained ODV exposure despite extensive VEN metabolism, and therefore suggest that ODV metabolism saturation may occur following large VEN overdoses.